Students’ Motivation To Learn English As Foreign Language (Efl): A Case Study - Wijayanti, Roro Anggun; Saraswati, Ria Saraswati; Santosa, Imam (JUPE : Jurnal Pendidikan Mandala, 2024)
This research aims to understand the factors influencing students' motivation to learn English as a foreign language (EFL) and their impact on academic performance. The study uses qualitative methods, including interviews and questionnaires, with a sample of grade 7 junior high school students in West Jakarta. The results show that intrinsic factors, such as interest in learning English and self-desire to achieve high academic achievement, are more motivating. However, extrinsic factors, such as teacher praise or parental expectations, can also influence intrinsic motivation. Thus, intrinsic factors have a more significant influence on students' motivation, while extrinsic factors also play a role. Understanding these factors can help build learning independence and improve students' academic performance.